Design, development and fluidic behavior analysis of triply periodic minimal surface (TPMS) based scaffolds for bone-applications - Kumar J.; Nirala N.S.; Singh N.K.; Gupta N.; Dwivedi Y.D.; Verma R.; Rai S.K.; Gupta M. (My University, 2025)
The fluidic behavior of porous scaffolds plays a vital role in the mass transportation of cells and the formation of new tissue, which is crucial for promoting bone ingrowth. TPMS porous structures are widely recognized in the field of tissue engineering as a versatile solution for designing biomorphic scaffolds due to their unique structural and biological properties. To explore the flow behavior of TPMS-based porous scaffolds, we employed a computational fluid dynamics (CFD) approach. Our study focused on two types of TPMS structures: I-graph wrapped package (IWP) and diamond (D); both were developed by using mathematically defined TPMS equations. For each structure, we created four model variants with porosities of 50%, 60%, 70%, and 80%, respectively. These models underwent systematic fluid flow simulations to evaluate important parameters such as permeability, wall shear stress (WSS), pressure distribution, velocity distribution, and pressure drop. These aspects are critical for assessing the suitability of scaffolds as bone substitutes. Our simulation results revealed that the IWP structure exhibited superior fluid accessibility compared to the diamond structure in terms of permeability and WSS. Overall, this investigation emphasizes the benefits of utilizing TPMS structures as a viable option for bone applications. The significant finding of this work underscores the importance of optimizing scaffold architecture to enhance cell ingrowth and transport phenomena at targeted anatomical sites. © The Author(s), under exclusive licence to Springer-Verlag France SAS, part of Springer Nature 2023.